How Labor Laws Can Transform Health Systems: The Case of Saudi Arabia - Yagoub Al-Mazrou; Taghreed Al-Ghaith; Abdo S. Yazbeck; Tamer S. Rabie (Taylor & Francis Group, 2017)
Abstract-In 1999, the Kingdom of Saudi Arabia enacted a law that compels private employers to cover non-Saudi employees with health insurance. In the 16 years that followed, the health sector in the Kingdom has seen a dramatic shift in how services are provided and paid for, and the change continues at an accelerated speed. Based on interviews with 12 large private sector providers in Riyadh, Jeddah, and Khobar, we found that a labor law enacted in 1999 led to rapid expansion of the insured population, both expatriates and Saudis, which led to a drastic change in how hospitals and other facilities are paid, and considerable more consistency in revenue stream. This article describes how the 1999 labor law, combined with other market conditions and public incentives, led to unprecedented growth in private sector capacity and how the insurance system changed the labor market for health care providers and put more pressure on physicians to engage in dual job holding in both the public and private sectors. The Kingdom later introduced another labor program, known as Nitaqat, designed to implement the Saudization initiative that started in 2011, which put pressure on all private companies to hire Saudi nationals. The interviews with large private health providers found the Nitaqat program to be the largest barrier to the growth of the sector. The Kingdom presents a striking case of how the health sector can be drastically impacted by laws and policies outside the sector and how health systems and reforms can, and should, take into account the whole range of policy instruments available to a country.